Catheter ablation is preferred over surgery for persistent atrial fibrillation. (22nd April 2020) - Anannab, Alisara; Gianni, Carola; Della Rocca, Domenico G; Sahore Salwan, Anu; Natale, Andrea; Al‐Ahmad, Amin
Abstract: There are important limitations that can hinder outcomes of surgical ablation in nonparoxysmal patients with atrial fibrillation (AF), which is the typical AF population undergoing concomitant cardiac surgery for valve or ischemic heart disease. Incomplete lesions with recovered conduction or gaps as well as arrhythmias originating from areas not targeted by surgical ablation are commonly seen at the time of recurrence. Therefore, while it might be reasonable to perform AF surgery in this cohort, it is important to know these limitations and establish adequate postoperative rhythm monitoring to detect recurrences, which can be effectively addressed by catheter ablation.